Replacing Missing Maxillary Lateral Incisors by CAD/CAM PMMA Cantilever Bridges - Shayma Karray; Yosra Gassara; Emna Boudabous; Sarra Nasri; Zohra Nouira; Hayet Hajjami (Case Reports in Dentistry)
Introduction. Management of missing maxillary lateral incisors can be a challenging endeavour for dentists. Whether from agenesis or tooth loss, several treatment modalities are currently present to tackle this task to ensure satisfactory aesthetics. Most patients, especially younger patients are more likely to prefer fixed prosthodontic rehabilitation. Among these options is the computer-aided design and computer-aided manufacturing polymethyl methacrylate (CAD/CAM PMMA) cantilever bridge. Case Descriptions. These two clinical cases describe the management of missing lateral maxillary incisors in two Tunisian female patients with different etiologies, using CAD/CAM PMMA cantilever bridge. Conclusions. CAD/CAM technologies allow for a fairly quick and simple try-in thanks to their high accuracy as well as being predictable, minimally invasive, and affordable treatment options. This type of restoration can be put to use for mid- to long-term solutions to missing maxillary lateral incisors. However, its success depends mainly on patient selection regarding age, general health, occlusal context, and proper indication.